Beach erosion and typhoons reduce green turtle nesting grounds on the Xisha Islands, South China Sea - Zhang, Ting; Zhang, Chenglong; Li, Yupei; Yu, Yangfei; An, Xiaoyu; Jiang, Yongkang; Wang, Jichao; Lin, Liu; Shi, Hai-Tao (Frontiers in Marine Science, 2024)
Introduction Sea turtles are ideal flagship and umbrella species for marine biodiversity conservation. The quality of nesting grounds is crucial for the successful reproduction of sea turtles, as it determines whether they can successfully nest and hatch. The Xisha Islands represent the largest remaining nesting grounds for green turtles in China. However, they face numerous threats and lack management guidelines for nesting ground restoration. Methods In this study, we continuously monitored the beach changes and coastal erosion on North Island, which is located in the northern region of the Xisha Islands, from 2019 to 2022. Results From 2020 to 2022, the beach area on North Island decreased annually by 11,800 m2, accounting for 24.39% of the beach area in 2020. The proportion of suitable nesting sand types (including coarse and medium sands) also decreased annually, with a reduction of 40–70% on the southern beach of North Island. The peak nesting period of green turtles on North Island coincides with the frequent occurrence of typhoons in the South China Sea, causing tidal surges that inundate green turtle nests, resulting in an average nest loss rate of 35.25%. Discussion Based on the above threats, it is recommended to promptly initiate habitat restoration in severely eroded areas of green turtle nesting grounds to prevent further declines in nesting area and quality. Additionally, measures such as nest relocation should be implemented to enhance green turtle reproductive success.